Pretreatment serum interleukin‐1β, interleukin‐6, and tumor necrosis factor‐α levels predict the progression of colorectal cancer. (22nd January 2016) - Chang, Pei‐Hung; Pan, Yi‐Ping; Fan, Chung‐Wei; Tseng, Wen‐Ko; Huang, Jen‐Seng; Wu, Tsung‐Han; Chou, Wen‐Chi; Wang, Cheng‐Hsu; Yeh, Kun‐Yun
Abstract: The correlations of pretreatment serum concentrations of proinflammatory cytokines such as interleukin (IL)‐1 β, IL‐6, and tumor necrosis factor‐ α (TNF α ) with the clinicopathologic features and progression of colorectal cancer (CRC) were investigated. The pretreatment serum levels of IL‐1 β, IL‐6, and TNF α were measured in 164 CRC patients before treatment. The relationships between changes in proinflammatory cytokine and C‐reactive protein (CRP) levels and both clinicopathologic variables and disease progression were examined by univariate and multivariate analysis. Advanced tumor stage was associated with a poorer histologic differentiation, higher CRP level, lower albumin level, and inferior progression‐free survival rate (PFSR). Furthermore, high levels of CRP (>5 mg/L) were associated with proinflammatory cytokine intensity, defined according to the number of proinflammatory cytokines with levels above the median level (IL‐1 β  ≥10 pg/mL; IL‐6 ≥ 10 pg/mL; and TNF α  ≥55 pg/mL). Under different inflammation states, proinflammatory cytokine intensity, in addition to tumor stage, independently predicted PFSR in patients with CRP <5 mg/L, whereas tumor stage was the only independent predictor of PFSR in patients with CRP ≥5 mg/L. Proinflammatory cytokine intensity and the CRP level are clinically relevant for CRC progression. Measurement of IL‐1 β, IL‐6, and TNF α serum levels may help identify early cancer progression among patients with CRP <5 mg/L in routine practice. Abstract : Proinflammatory cytokine intensity is clinically relevant for CRC progression. Measurement of IL‐1 β, IL‐6, and TNF α serum levels may help identify early cancer progression among patients with normal CRP level.